Classical phase synchronization in dissipative non-Hermitian coupled systems - Rohn, Jonas; Schmidt, Kai Phillip; Genes, Claudiu (Physical Review A, 2023)
We study the interplay between non-Hermitian dynamics and classical phase synchronization in a system of N bosonic modes commonly coupled to an auxiliary, driven mode. For any set of non-Hermitian bipartite interactions between the auxiliary and other modes, the system evolves towards a phase synchronized state. We provide analytical and numerical evidence of such classical phase synchronization for systems ranging from a few modes to the macroscopic limit of large N and analyze the effects of inhomogeneous frequency broadening and robustness under the action of external thermal noise.
CRIS-Team Scopus Importer:2023-09-08